The impact of primary tumor sidedness on survival in early‐onset colorectal cancer by stage: A National Veterans Affairs retrospective analysis. (2nd April 2021) - Azar, Ibrahim; Al Masalmeh, Nada; Esfandiarifard, Saghi; Virk, Gurjiwan; Kiwan, Wissam; Frank Shields, Anthony; Mehdi, Syed; Philip, Philip A.
Abstract: Background: The incidence of early‐onset colorectal cancer (EOCRC) is rising. Left‐sided colorectal cancer (LCC) is associated with better survival compared to right‐sided colon cancer (RCC) in metastatic disease. NCCN guidelines recommend the addition of EGFR inhibitors to KRAS/NRAS WT metastatic CRC originating from the left only. Whether laterality impacts survival in locoregional disease and EOCRC is of interest. Methods: 65, 940 CRC cases from the National VA Cancer Cube Registry (2001–2015) were studied. EOCRC (2096 cases) was defined as CRC diagnosed at <50 years. Using ICD codes, RCC was defined from the cecum to the hepatic flexure (C18.0–C18.3), and LCC from the splenic flexure to the rectum (C18.5–18.7; C19 and C20). Results: EOCRC is more likely to originate from the left side (66.65% LCC in EOCRC vs. 58.77% in CRC). Overall, LCC has better 5‐year Overall Survival (OS) than RCC in stages I (61.67% vs. 58.01%) and III (46.1% vs. 42.1%) and better 1‐year OS in stage IV (57.79% vs. 49.49%). Stage II RCC has better 5‐year OS than LCC (53.39% vs. 49.28%). In EOCRC, there is no statistically significant difference between LCC and RCC in stages I‐III. Stage IV EOCRC patients with LCC and RCC have a 1‐year OS of 73.23% and 59.84%, respectively. Conclusion: In EOCRC, LCC is associated with better OS than RCC only stage IV. In the overall population, LCC is associated with better OS in all stages except stage II. The better prognosis of stage II RCC might be due to the high incidence of mismatch repair deficient tumors in this subpopulation. Abstract : In EOCRC patients, LCC is associated with better OS than RCC only in patients with metastatic disease. In the overall population, LCC is associated with better OS in all stages except stage II, which might be due to the high incidence of MMRd tumors in this subpopulation.